Trwałość społeczno-ekonomiczna a zmiany w ukształtowaniu przestrzeni produkcyjnej gospodarstw rolnych - Kuśmierz-Gozdalik, Urszula (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2000)
The purpose of the study presented in this paper was to answer the question whether the consolidated agricultural holdings have essential advantage over these spatially handicapped, in view of the demographic evolution and changes both in labour resources and labour efficiency. The research outcomes proved hypothetical advantage. The land consolidation led to: (i) the improvement in the ratio between the younger and elder farmers, (ii) the increase in the number of more educated peoples, especially at the general and specialised non-agricultural secondary level. The above mentioned tendencies were observed particularly in the villages characterised by higher soil quality and faced by more favourable economic and social conditions as well as market ones. lt was found that land consolidation created the opportunities to more rational resources allocation on farm and to shifting family labour surpluses into other economic activities including new ones. Apparently, the quick implementation of arranging works would give the chance to combine the process of agriculture modernisation with multifunctional rural development in Lublin Region.